The The Level of Knowledge, Perception, and Attitudes of Community Pharmacist in Yogyakarta City - Candradewi, susan Fitria; Putri, Wiwin Nopita; Hidayati, Ana (Jurnal Farmasi Udayana; Vol. 11, No. 2, Tahun 2022, 2023)
The Corona virus found in Wuhan gives challenges for health workers such as pharmacists who are responsible for providing education to the public, especially regarding COVID 19. The aim of the study was to measure the level of knowledge, perceptions and attitudes of  community pharmacists in Yogyakarta regarding COVID-19. The research design was analytic observational with a population of pharmacists who practiced in community pharmacies in  Yogyakarta  and the sample was a community pharmacists who practiced for at least 6 months. The results showed that community pharmacists in Yogyakarta had good knowledge about COVID-19 (60%) and 40% of them had sufficient knowledge. Pharmacists who have a positive perception was 66% and who have a negative perception was 34%. The attitude of pharmacists shows 68% positive and 32% negative. The relationship between education level and pharmacist's knowledge, perception and attitude obtained p-values ??of 0.241, 0.806 and 0.094, respectively, while the relationship between length of work experience and pharmacist's knowledge, perceptions and attitudes obtained p-values ??of 0.010, 0.352, and 0.022, respectively. The conclusion of this study is that pharmacists at the Yogyakarta City pharmacy have good knowledge, positive perceptions and attitudes about COVID-19 and there is a relationship between length of work experience and knowledge and attitudes (p<0.05).